2010
DOI: 10.3390/v2112409
|View full text |Cite
|
Sign up to set email alerts
|

Development of ST-246® for Treatment of Poxvirus Infections

Abstract: ST-246 (Tecovirimat) is a small synthetic antiviral compound being developed to treat pathogenic orthopoxvirus infections of humans. The compound was discovered as part of a high throughput screen designed to identify inhibitors of vaccinia virus-induced cytopathic effects. The antiviral activity is specific for orthopoxviruses and the compound does not inhibit the replication of other RNA- and DNA-containing viruses or inhibit cell proliferation at concentrations of compound that are antiviral. ST-246 targets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
71
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 72 publications
(89 reference statements)
6
71
0
Order By: Relevance
“…The mechanism of action of ST-246 appears to be similar to IMCBH in that drug resistant mutations mapped to F13L, however ST-246 was very active in animal models of vaccinia, cowpox, ectromelia, monkeypox, and variola virus infections (Jordan et al, 2010). This mechanism of action confirmed that the formation of EEV was important in the pathogenesis of orthopoxviruses and is consistent with genetic data that indicated that the inhibition of EEV production was sufficient to limit the spread of infection in vivo and prevent mortality (Jordan et al, 2010; Payne and Kristensson, 1985). …”
Section: Potential Molecular Targets In Orthopoxvirus Replication supporting
confidence: 86%
“…The mechanism of action of ST-246 appears to be similar to IMCBH in that drug resistant mutations mapped to F13L, however ST-246 was very active in animal models of vaccinia, cowpox, ectromelia, monkeypox, and variola virus infections (Jordan et al, 2010). This mechanism of action confirmed that the formation of EEV was important in the pathogenesis of orthopoxviruses and is consistent with genetic data that indicated that the inhibition of EEV production was sufficient to limit the spread of infection in vivo and prevent mortality (Jordan et al, 2010; Payne and Kristensson, 1985). …”
Section: Potential Molecular Targets In Orthopoxvirus Replication supporting
confidence: 86%
“…Both these drugs had similar mechanisms of antiviral action, which were associated with blocking the process of formation of the virion envelope in infected cells negatively influencing the formation of a pathogenetically significant extracellular enveloped virus (Jordan et al, 2010;Shishkina et al, 2015). ICR mice were given orally 0.2 ml of suspension of these compounds at the dose of 60 mg (g body weight)…”
mentioning
confidence: 99%
“…CMX001 converts to cidofovir in vivo , and thus has the same mode of action. ST-246 is a unique compound that blocks a late step in virus assembly by preventing intracellular envelope virus formation and subsequent virus egress from the cell [19,20]. This greatly restricts the spread of virus in vivo .…”
Section: Efficacy Of Antiviral Compounds In Animal Modelsmentioning
confidence: 99%